Optimizing Series-Parallel Execution of Intersecting Blocks of Operations. Issue 3 (2015) - Dolgui, Alexandre; Levin, Genrikh; Rozin, Boris
Abstract: A collection of intersecting blocks of operations is executed successively and all operations of each block are executed in parallel. The intensities of execution of operations to be defined remain invariable for all blocks that include these operations. Cost and time expenses for execution of operations depend on their volumes and intensities. Additional expenses for execution of operation block are proportional to the duration of this block. The problem is to define the intensities of all operations minimizing the total cost under constraint on the total collection duration. The methods for two particular cases of the problem are proposed.